2016
DOI: 10.1111/1753-0407.12452
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c levels are associated with severity of hypoxemia and not with apnea hypopnea index in patients with type 2 diabetes: Results from a cross‐sectional study

Abstract: The presence of sleep apnea is associated with poorer glycemic control in patients with T2D. In patients with sleep apnea and T2D, greater levels of oxygen desaturation are associated with poorer glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
10
2
4
Order By: Relevance
“…After adjustment for age, gender, diabetes duration, diabetes treatment, and body mass index, HbA1c was associated with mean and lowest O 2 saturation during sleep (β = −0.23 [ P = 0.03] and β = −0.24 [ P = 0.007], respectively). Further adjustment for waist circumference showed that HbA1c was independently associated only with the lowest O 2 saturation during sleep (β = −0.21; P = 0.05) . We did not observe any association between the apnea–hypopnea index and HbA1c …”
contrasting
confidence: 61%
See 3 more Smart Citations
“…After adjustment for age, gender, diabetes duration, diabetes treatment, and body mass index, HbA1c was associated with mean and lowest O 2 saturation during sleep (β = −0.23 [ P = 0.03] and β = −0.24 [ P = 0.007], respectively). Further adjustment for waist circumference showed that HbA1c was independently associated only with the lowest O 2 saturation during sleep (β = −0.21; P = 0.05) . We did not observe any association between the apnea–hypopnea index and HbA1c …”
contrasting
confidence: 61%
“…Further adjustment for waist circumference showed that HbA1c was independently associated only with the lowest O 2 saturation during sleep (β = −0.21; P = 0.05) . We did not observe any association between the apnea–hypopnea index and HbA1c …”
contrasting
confidence: 61%
See 2 more Smart Citations
“…Rusu et al 1 evaluated the relationship between untreated sleep apnea syndrome (SAS) and glycemic control in patients with type 2 diabetes (T2D). Among 100 patients with T2D, 64 patients had untreated SAS.…”
mentioning
confidence: 99%